2020
DOI: 10.25299/sportarea..vol().5092
|View full text |Cite
|
Sign up to set email alerts
|

Profil Mood Atlet Pra-Pon Sepak Takraw Puteri Sulawesi Tengah Dalam Melakukan Latihan

Abstract: The research was conducted to find out how much the mood of female pre-PON sepak takraw athletes in Sulawesi Tengah after doing the exercises and how the mood condition of the female pre-PON athletes after conducting the training. The method in this research is a survey research. The population of this study is 10 people, namely the pre-PON Sepak Takraw athletes of the women of Sulawesi Tengah with the sampling technique using total sampling. The collecting technique of data is a questionnaire using the rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…If athletes have high self-confidence then they can strengthen the team because with self-confidence they can emit positive emotions which have a big influence on the surrounding environment. With athletes who are confident, they can be calmer and concentrate better when training so they don't get tense when competing or doing extra routine training (Wahyudi & Fajarwati, 2020). This category indicates that the athlete has a sufficient level of self-confidence and is able to carry out the task well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If athletes have high self-confidence then they can strengthen the team because with self-confidence they can emit positive emotions which have a big influence on the surrounding environment. With athletes who are confident, they can be calmer and concentrate better when training so they don't get tense when competing or doing extra routine training (Wahyudi & Fajarwati, 2020). This category indicates that the athlete has a sufficient level of self-confidence and is able to carry out the task well.…”
Section: Discussionmentioning
confidence: 99%
“…The research was conducted for one month, where athletes were asked to fill out the Profile Of Mood States (POMS) questionnaire with a rating scale. The POMS questionnaire used is the Indonesian version (Wahyudi & Fajarwati, 2020) which consists of thirty-five statement items with seven indicators. Data collection was carried out by adding up all scores per indicator and analyzed using statistical analysis techniques.…”
Section: Metodmentioning
confidence: 99%
See 1 more Smart Citation
“…The mood has a broad influence on perception, motivation and behavior. 5,6 A previous study conducted by Kawano et al (2012), reported that oxygen consumption during jump rope training (movement skill training that is consist of floating stage and a landing stage carried out continuously and repeatedly) has reached more than 70% of the maximum oxygen consumption. This shows that jump rope training is one type of aerobic.…”
Section: Introductionmentioning
confidence: 99%